Guillain-Barré syndrome: expanding the concept of molecular mimicry. Issue 4 (April 2022) - Laman, Jon D.; Huizinga, Ruth; Boons, Geert-Jan; Jacobs, Bart C.
Abstract : Guillain-Barré syndrome (GBS) is a rapidly progressive, monophasic, and potentially devastating immune-mediated neuropathy in humans. Preceding infections trigger the production of cross-reactive antibodies against gangliosides concentrated in human peripheral nerves. GBS is elicited by at least five distinct common bacterial and viral pathogens, speaking to the notion of polymicrobial disease causation. This opinion emphasizes that GBS is the best-supported example of true molecular mimicry at the B cell level. Moreover, we argue that mechanistically, single and multiplexed microbial carbohydrate epitopes induce IgM, IgA, and IgG subclasses in ways that challenge the classic concept of thymus-dependent (TD) versus thymus-independent (TI) antibody responses in GBS. Finally, we discuss how GBS can be exemplary for driving innovation in diagnostics and immunotherapy for other antibody-driven neurological diseases. Highlights: Guillain-Barré syndrome (GBS) after Campylobacter jejuni infection is a true case of molecular mimicry–driven disease. The immunopathogenesis of GBS sheds new light on the multimolecular identities of self-antigens. The glycan nature of mimicry epitopes that drives antibody class switching to IgG subclasses challenges rigid concepts of thymus-dependent and -independent B cell responses because antiglycolipid antibodies are mainly IgG1 and IgG3, albeit short-lasting. Combinatorial chemoenzymatic technologies and arrays allow the development of novel diagnostic and research tools to identify antibodies against mono- and multimeric carbohydrate epitopes. A certain degree of dissimilarity may be required for the occurrence of molecular mimicry in Campylobacter jejuni –associated GBS.